Postburn Reconstruction of the Face and Neck. Issue 6 (29th November 2022) - Sabapathy, S. Raja; Shanmugakrishnan, R. Raja; Ramkumar, Sanjai; Muthukumar, Vamseedharan; Senthilkumaran, M.; Bharathi, R. Ravindra
Abstract : Learning Objectives: After studying this article, the participant should be able to: 1. Understand the cardinal principles in the management of postburn deformities in the face and neck. 2. Understand reconstruction of specific subsites in the face and neck affected by burn contracture. 3. Acquire knowledge about the various techniques of burn reconstruction of the face and neck. 4. Grasp technical nuances and select appropriate surgical options for individual cases. Summary: Postburn contractures in the face and neck region are multifactorial in origin and difficult to prevent in extensive burns. Facial burns lead to distortion of anatomical landmarks, causing aesthetic, functional, and psychological problems. Each subunit of the face is unique in structure; thus, the surgeon needs to adjust the timing of surgery and the technique according to region and the severity of contracture. Contracture of one unit, especially that of the neck and forehead, can exaggerate the contracture in neighboring subunits. The role of these extrinsic influences must be considered while sequencing surgical procedures. The burn surgeon must be adept in all reconstructive surgery techniques from skin grafting to tissue expanders to microsurgery to obtain the best outcomes. Surgery must be followed up with long-term physical therapy and psychological rehabilitation to help burn survivors with head and neck contractures to integrate back into society.